2020
DOI: 10.1101/2020.09.03.280651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Essentiality of c-di-AMP inBacillus subtilis: Bypassing mutations converge in potassium and glutamate homeostasis

Abstract: In order to adjust to changing environmental conditions, bacteria use nucleotide second messengers to transduce external signals and translate them into a specific cellular response. Cyclic di-adenosine monophosphate (c-di-AMP) is the only known essential nucleotide second messenger. In addition to the well-established role of this second messenger in the control of potassium homeostasis, we observed that glutamate is as toxic as potassium for a c-di-AMP-free strain of the Gram-positive model bacterium Bacill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
(74 reference statements)
0
2
0
1
Order By: Relevance
“…This is known as bypass of essentiality (BoE), with systematic studies of essential gene bypass having been conducted in yeast (Li et al ., 2019; van Leeuwen et al ., 2020). BoE has been shown for several essential genes in bacteria including zipA , c-di-AMP null mutants, RNase E, bamD , and ftsH (Anupama et al ., 2011; Pichoff et al ., 2015; Krüger et al ., 2021; Wang et al ., 2021; Hart and Silhavy, n.d.). Utilizing a BoE screen we were able to isolate eight double mutants capable of tolerating erfRP deletion (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…This is known as bypass of essentiality (BoE), with systematic studies of essential gene bypass having been conducted in yeast (Li et al ., 2019; van Leeuwen et al ., 2020). BoE has been shown for several essential genes in bacteria including zipA , c-di-AMP null mutants, RNase E, bamD , and ftsH (Anupama et al ., 2011; Pichoff et al ., 2015; Krüger et al ., 2021; Wang et al ., 2021; Hart and Silhavy, n.d.). Utilizing a BoE screen we were able to isolate eight double mutants capable of tolerating erfRP deletion (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Both GltP and GltT belong to the dicarboxylate/amino acid:cation (Na + or H + ) symporter family (Slotboom et al, 1999;Saier et al, 2000b). It is interesting to note that the suppressor screen by Wicke and co-workers (Wicke et al, 2019) did not led to the inactivation of the aimA gene that was recently shown to encode the major glutamate transporter AimA in B. subtilis (Krüger et al, 2021). It is tempting to speculate that AimA has a higher specificity for transporting glutamate as compared to GltT and GltP.…”
Section: Glyphosate Resistance Due To Decreased Uptake and Increased Exportmentioning
confidence: 99%
“…Glutamat, sie hemmen die Aufnahme der beiden Ionen oder stimulieren den Abbau von Glutamat. Grüner Stern: aktivierende Mutation; roter Stern: inaktivierende Mutation (modifi ziert aus [11]).…”
Section: C-di-amp Bindet Protein-und Rna-moleküleunclassified